2019
DOI: 10.1021/acs.est.9b03427
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Transport of Terrestrial Microplastics to the Ocean through Atmosphere

Abstract: Although atmospheric transport and deposition could be an important pathway of terrestrial pollutants to the ocean, little information concerning the presence and distribution of these suspended atmospheric microplastics in marine air is available. We investigated, for the first time, the occurrence and distribution of suspended atmospheric microplastics (SAMPs) in the west Pacific Ocean. In this study, the spatial distribution, morphological appearance, and chemical composition of suspended atmospheric microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(173 citation statements)
references
References 26 publications
5
146
1
1
Order By: Relevance
“…Our findings indicate a new possible source and formation mechanism for AMP, different to those found for the terrestrial and coastal AMP detected to date 13,[22][23][24][25][26][27][28][29][30][31][32][33] . We have evidence from the open ocean, which suggest that AMP is emitted from the seawater into the atmosphere through wind related processes.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…Our findings indicate a new possible source and formation mechanism for AMP, different to those found for the terrestrial and coastal AMP detected to date 13,[22][23][24][25][26][27][28][29][30][31][32][33] . We have evidence from the open ocean, which suggest that AMP is emitted from the seawater into the atmosphere through wind related processes.…”
Section: Resultscontrasting
confidence: 71%
“…Estimates of recent years suggest that ∼5.25 trillion plastic fragments are currently floating on the oceans' surface 21 . Airborne microplastic particles (AMP) from terrestrial origins were found in both polluted and remote areas over land, as well as in coastal regions, ranging from micron to mm scales, and can travel tens of kilometers 12,13,[22][23][24][25][26][27][28][29][30][31][32][33] . However, despite the overwhelming amounts of marine MP and their effect on the marine environment, atmospheric microplastic particles over the ocean are given little attention 13 .…”
mentioning
confidence: 99%
“…9721)). Besides, the active collection requires a pump for aspiration of air through filters with well-defined mesh, as usually performed for atmospheric particulate matter [53,54] and as described for airborne MP [37,42,55]; sampling devices with sequential filters with decreasing mesh size are also available (cascade impactor). Commonly, to avoid contaminations, sampling is performed using quartz fiber or polytetrafluoroethylene filters.…”
Section: Samplingmentioning
confidence: 99%
“…Indeed, both hydrogen peroxide and the Fenton reaction produce hydroxyl radicals, which were shown to react efficiently with some NP [50]. For this reason, separation and purification steps have not been employed in several studies, however this might increase the difficulties in the detection and the identification of MP [34,37,42,55].…”
Section: Purificationmentioning
confidence: 99%
See 1 more Smart Citation